The effectiveness of Valsalva Maneuver-Assisted percutaneous vertebroplasty in reducing cement leakage in osteoporotic vertebral compression fractures - Yongjie Wang; Xueming Chen; Qian Lu; Libin Cui; Xiangyu Li; Chao Kong; Shibao Lu (BMC Musculoskeletal Disorders)
Abstract Objectives Percutaneous vertebroplasty (PVP) is a highly practical treatment of osteoporotic vertebral compression fractures (OVCFs). However, cement leakage (CL) after PVP remains a challenging problem. There is a lack of effective methods to reduce CL. The objective of this study is to evaluate the effectiveness and safety of Valsalva maneuver-assisted percutaneous vertebroplasty (V-PVP) compared to conventional PVP in treating OVCFs. Methods 302 patients were enrolled in this study. Patients were divided into the V-PVP group and the conventional PVP group according to whether they received the Valsalva maneuver intraoperatively. Postoperative CT was performed to determine CL which can be classified as no leakage, cortical leakage, venous leakage, and cortical & venous leakage. CL rate and visual analog scale (VAS), performed before surgery, 1 day, and 6 months after surgery, Operation time, cement volume, pulmonary embolism rate, and hospital stay were compared between the two groups. The age, gender, BMI, BMD, fracture segment (thoracic, thoracolumbar, lumbar), fracture type (mild, moderate), cortical disrupture and cement volume of the two groups were also recorded, Multinomial Logistic regression analysis of all factors was conducted to analyze the relationship between all factors and CL. Results A total of 302 patients were enrolled (150 V-PVP and 152 PVP). The V-PVP group had significantly lower overall CL rates (36.7% vs. 77.6%), lower pulmonary embolism rates (1.3% vs. 17.1%), and shorter hospital stays. Pain relief was significantly better in the V-PVP group at 1 day and 6 months post-surgery (P < 0.01). Logistic regression analysis identified male gender and absence of cortical disruption as protective factors against cortical leakage, while Genant grade 2 was a risk factor. Male gender and V-PVP treatment were protective against venous leakage, whereas thoracic fractures and higher BMD were risk factors. No significant differences were found in operation time or cement volume between the groups. Conclusion V-PVP is a more effective and safer option than conventional PVP for treating OVCFs, particularly in reducing cement leakage and pulmonary embolism rates. Future prospective studies with larger sample sizes are warranted to validate these findings.